Diversity of Amphibians and Reptiles in Various Anthropogenic Disturbance Habitats in Nantu Forest, Sulawesi, Indonesia - Mirza Dikari Kusrini; Luna Raftika Khairunnisa; Aria Nusantara; Agus Priyono Kartono; Lilik Budi Prasetyo; Novi Tri Ayuningrum; Fata Habiburrahman Faz (Jurnal Manajemen Hutan Tropika, 2020)
The Nantu Forest in Gorontalo Province, Sulawesi, Indonesia holds one of the few remaining pristine habitats in the island. The reserve is surrounded by human habituation which provide opportunity to study the impact of forest lost on biodversity. In addition, data on Nantu mostly focused on big mammals, as there is no previous herpetofauna survey at the area. Sampling of amphibian and reptile was conducted in June 2013 and in May–June 2014 using Visual Encounter Survey method, glue traps and transect sampling in seven different sites at the eastern part of Nantu. We categorized four habitat types based on human disturbances: high disturbed habitat (HDH), moderate disturbed habitat (MDH), low disturbed habitat (LDH) and pristine habitat (PH). A total of 680 individual amphibians (4 families; 17 species) and 119 individual reptiles (9 families; 29 species) were recorded. Species richness and species composition for amphibians and reptiles differs according to the level of human disturbances. Low level disturbances habitat demonstrated the highest diversity of amphibians and reptiles, whereas as expected, high distubed habitat showed the lowest diversity. Anthropogenic pressures in forest will decrease species richness of amphibian and reptiles. Although most amphibian and reptiles will be able to persist in low disturbances habitat, forest-dependent species will be lost when pristine forests are disturbed.